# Class 12 RD Sharma Solutions – Chapter 11 Differentiation – Exercise 11.4 | Set 2

• Last Updated : 13 Jan, 2021

### Question 16. If x√(1+y) +y√(1+x) =0  then prove that (1+x)2dy/dx +1=0

Solution:

We have,

Hey! Looking for some great resources suitable for young ones? You've come to the right place. Check out our self-paced courses designed for students of grades I-XII

Start with topics like Python, HTML, ML, and learn to make some games and apps all with the help of our expertly designed content! So students worry no more, because GeeksforGeeks School is now here!

x√(1+y) +y√(1+x) =0

=>x√(1+y)=-y√(1+x)

On squaring both sides, we have

x2(1+y)=y2(1+x)

=>x2+ x2y-y2-y2x=0

=>(x+y)(x-y)+xy(x-y)=0

=>(x-y)(x+y+xy)=0

So, either (x-y)=0

or, x+y+xy=0

=>x+y(1+x)=0

=>y=-x/(1+x)

On differentiating both sides with respect to x,

dy/dx=d(-x/(1+x))/dx

On applying quotient rule,

dy/dx = ((x)1-(1+x))/(1+x)2

=>dy/dx=(-1/(1+x)2)

=>(dy/dx)(1+x)2+1=0

Hence, proved.

### Question 17. log(√(x2+y2)) = tan-1(y/x)

Solution:

We have,

log(√(x2+y2))=tan-1(y/x)

=>log(x2+y2)(1/2)=tan-1(y/x)

=>(1/2)(log(x2+y2))=tan-1(y/x)

On differentiating both sides with respect to x,

(1/2)d(log(x2+y2))/dx = d(tan-1(y/x))/dx

=>(1/2)*(1/(x2+y2))*(2x+2y(dy/dx))=1/(1+(y/x)2)((x(dy/dx)-y)/x2)

=>x+y(dy/dx)=x(dy/dx)-y

=>(dy/dx)(y-x)=-(x+y)

=>(dy/dx)=(x+y/(x-y)

(dy/dx)=(x+y)/(x-y)

### Question 18. sec((x+y)/(x-y)) = a

Solution:

We have,

sec((x+y)/(x-y))=a

=>(x+y)/(x-y)=sec-1(a)

On differentiating both sides with respect to x,

=>d((x+y)/(x-y))/dx=d(sec-1(a))/dx

=>(x-y)(1+(dy/dx))-(x+y)(1-(dy/dx))=0(x-y)2

=>x-y+(x-y)(dy/dx)-(x+y)+(x+y)(dy/dx)=0

=>(dy/dx)(x-y+x+y)-2y=0

=>(dy/dx)(2x)=2y

=>(dy/dx)=(y/x)

(dy/dx)=(y/x)

### Question 19. tan-1((x2-y2)/(x2+y2)) = a

Solution:

We have,

tan-1((x2-y2)/(x2+y2))=a

=>(x2-y2)/(x2+y2)=tan a

=>(x2-y2)=(tan a)(x2+y2)

On differentiating both sides with respect to x,

=>d(x2-y2)dx=d((tan a)(x2+y2))/dx

=>2x-2y(dy/dx)=(tan a)(2x+2y(dy/dx))

=>x-y(dy/dx)=(tan a)(x+y(dy/dx))

=>-(dy/dx)(y+y(tan a))=x(tan a)-x

=>-(dy/dx)=(x(tan a-1))/(y(1+tan a))

=>dy/dx= (x(1-tan a))/(y(1+tan a))

dy/dx =(x(1-tana))/(y(1+tan a))

### Question 20. xy(log(x+y)) = 1

Solution:

We have,

xy(log(x+y))=1

Differentiating it with respect to x,

d(xy(log(x+y)))/dx =d1/dx

=>y(log(x+y))+x(log(x+y)dy/dx+((xy)/(x+y))(1+(dy/dx)))=0

=>y(log(x+y))+((xy)/(x+y))+(dy/dx)(x(log(x+y))+(xy)/(x+y))=0

=>(dy/dx)(x(log(x+y))+(xy)/(x+y))=-(y(log(x+y))+(xy)/(x+y))

It can be deduced that ,

y(log(x+y))=1/x

x(log(x+y))=1/y

So,

(dy/dx)((1/y)+(xy)/(x+y))=-((1/x)+(xy)/(x+y)

=>(dy/dx)((x+y+xy2)/((y+y)x))=-(x+y+x2y)/(y)(x+y))

=>(dy/dx)=-((x+y+x2y)/(x+y+xy2))(y/x)

dy/dx=-((x(x2y+x+y))/(y(xy2+x+y)))

### Question 21. y = xsin(a+y)

Solution:

We have,

y=x sin(a+y)

Differentiating it with respect to x,

dy/dx=sin(a+y) +x*cos(a+y){0+dy/dx}

=>dy/dx =sin(a+y) +x*cos(a+y)*(dy/dx)

=>dy/dx-x*cos(a+y)*(dy/dx) =sin(a+y)

=>(dy/dx)(1-x*cos(a+y))=sin(a+y)

=>dy/dx=(sin(a+y))/(1-x*cos(a+y))

dy/dx =(sin(a+y))/(1-x*cos(a+y))

### Question 22. x*sin(a+y)+(sin a)*(cos(a+y)) = 0

Solution:

We have,

x*sin(a+y)+(sin a)*(cos(a+y))=0

On differentiating both sides with respect to x,

d(x*sin(a+y)+(sin a)*(cos(a+y)))/dx=d0/dx

=>sin(a+y)+x*cos(a+y)*(dy/dx)-(sin a)sin(a+y)(dy/dx)=0

=>(dy/dx)(xcos(a+y)-sina(sin(a+y)))=-sin(a+y)

=>(dy/dx)=sin(a+y)/(sina*sin(a+y)-xcos(a+y))

From above,

x=-((sina)*cos(a+y))/sin(a+y)

Putting in the above equation,

(dy/dx)*(((sina)*cos2(a+y))/(sin(a+y)))+(sina)sin(a+y))=sin(a+y)

(dy/dx)((sina)((cos2(a+y)+sin2(a+y))/sin(a+y)) =sin(a+y)

(dy/dx)=(sin2(a+y))/(sin a)

(dy/dx)=sin2(a+y)/(sina)

### Question 23. y = x*siny

Solution:

We have,

y=x*siny

On differentiating both sides with respect to x,

dy/dx=siny+x(cosy)(dy/dx)

=>dy/dx-x(cosy)(dy/dx)=siny

=>(dy/dx)(1-x(cosy))=siny

=>dy/dx=(siny)/(1-x(cosy))

(dy/dx)=(siny)/(1-x(cosy))

### Question 24. y(x2+1)1/2 = log((x2+1)1/2-x)

Solution:

We have,

y(x2+1)1/2=log((x2+1)1/2-x)

Differentiating it with respect to x,

d(y(x2+1)1/2)/dx=(((x2+1)1/2-x)-1/2)(2(x2+1))-1/2(2x-1)

=>2xy(2(x2+1)-1/2)+(x2+1)1/2(dy/dx)=(((x2+1)1/2-x)-1/2)(x-(x2+1)1/2)(x2+1))-1/2

=>(dy/dx)(x2+1)1/2=((((x2+1)1/2-x)-1/2)(x-(x2+1))-1/2x)/(x2+1))-(xy)(x2+1)-1/2

=>(dy/dx)(x2+1)1/2=(-1/(x2+1)1/2)-(xy)(x2+1)-1/2

=>(dy/dx)(x2+1)1/2=(-1-xy)(x2+1)-1/2

=>(dy/dx)(x2+1)=-(1+xy)

=>(dy/dx)(x2+1)+xy+1=0

(dy/dx)(x2+1)+xy+1=0

### Find dy/dx at x=pi/4

Solution:

We have,

y=(logcosxsinx)(logsinxcosx)-1+sin-1(2x/(1+x2))

=>y=(logcosxsinx)(logcosxsinx)+sin-1(2x/(1+x2))

=>y=(logcosxsinx)2+sin-1(2x/(1+x2))

=>y=((log sinx)/log(cosx))2+sin-1(2x/(1+x2))

Differentiating it with respect to x,

dy/dx=d((log sin x)/log(cos x))2/dx+ d(sin-1(2x/(1+x2)))

=>dy/dx =2((log sinx)/log(cosx))d((log sinx)/(log cosx))/dx+1/(√1-((2x)/(1+x2))2d(2x/(1+x2))/dx

=>dy/dx=2((log sinx)/log(cosx))*((log cosx)(1/sin x)*(cos x)-(log sinx)*(1/cosx)*(-sinx))/(log(cosx))2 +((1+x2)/√(1+x4-2x2))((1+x2)2-4x2)/(1+x2)2

=>dy/dx=2(log sinx)/(logcosx)*((log cosx)*cotx+(log sinx)tanx)+((1+x2)/√(1-x2)2)(1-2x2)/(1+x2)2

=>dy/dx=(2(log sinx)*((log cosx)cotx+(log sinx)tanx))/(log cosx)3+2/(1+x2)

At x=pi/4

dy/dx=(2(log sin(pi/4))*((log(cos(pi/4) cot(pi/4)+(log sin(pi/4))tan(pi/4))/(log cos(pi/4))3+2/(1+(pi2)/16)

=>dy/dx=2(log(1/√2))*(log(1/√2)+log(1/√2))/(log(1/√2))3+32/(16+(pi)2)

=>dy/dx=4(1/(log(1/√2)))+32/(16+(pi)2)

=>dy/dx=4(1/((-1/2)log2)+32/(16+(pi)2)

=>dy/dx=32/(16+(pi)2)-8(1/log2)

(dy/dx)=32/(16+(pi)2)-8(1/log2)

### Question 26. sin(xy)+y/x = x2-y2

Solution:

We have,

sin(xy)+y/x=x2-y2

Differentiating it with respect to x,

d(sin(xy)+d(y/x))/dx =d(x2)/dx -d(y2)/dx

=>cos(xy)(x(dy/dx)+y) +(x(dy/dx)-y)(x-2)=2x-2y(dy/dx)

=>x*cos(xy)(dy/dx) + ycos(xy)+(x-1)(dy/dx)-y(x-2)+2y(dy/dx)=2x

=>(dy/dx)(x*cos(xy)+x-1+2y)=2x-ycos(xy)-y(x-2)

=>dy/dx=(2x-ycos(xy)-y(x-2))/(x*cos(xy)+x-1+2y)

(dy/dx)=(2x-ycos(xy)-y(x-2))/(x*cos(xy)+x-1+2y)

### Question 27. (y+x)1/2+(y-x)1/2 = c

Solution:

We have,

(y+x)1/2+(y-x)1/2=c

Differentiating it with respect to x,

(1/2)(y+x)-1/2((dy/dx)+1) + (1/2)(y-x)-1/2((dy/dx)-1)=0

=>(dy/dx)((1/2)(y+x)-1/2+(1/2)(y-x)-1/2) +(1/2)(y+x)-1/2-(1/2)(y-x)-1/2=0

=>(dy/dx)=((y-x)-1/2-(y+x)-1/2)/((y+x)-1/2+(y-x)-1/2)

By rationalisation of denominator,

(dy/dx)=(y+x)+(y-x)-2(y+x)1/2(y-x)1/2

=>dy/dx=(2y-2(y+x)1/2(y-x)1/2)/(x+y-y+x)

=>dy/dx=(y-((y2-x2)1/2)/(x)

dy/dx=(y-((y2-x2)1/2)/(x)

### Question 28. tan(x+y)+tan(x-y) = 1

Solution:

We have,

tan(x+y)+tan(x-y)=1

Differentiating it with respect to x,

d(tan(x+y)+tan(x-y))/dx=d1/dx

=>sec2(x+y)(d(x+y)/dx)+sec2(x-y)d(x-y)/dx=0

=>sec2(x+y)(1+dy/dx)+sec2(x-y)(1-dy/dx)=0

=>(dy/dx)(sec2(x+y)-sec2(x-y))+sec2(x+y)+sec2(x-y)=0

=>dy/dx=(sec2(x+y)+sec2(x-y))/(sec2(x-y)-sec2(x+y))

dy/dx=(sec2(x+y)+sec2(x-y))/(sec2(x-y)-sec2(x+y))

### Question 29. ex+ey = ex+y

Solution:

We have,

d(ex+ey)/dx=de(x+y)/dx

=>ex+ey(dy/dx)=e(x+y)(1+(dy/dx))

=>(dy/dx)(ey-e(x+y))=e(x+y)-ex

=>(dy/dx)=(e(x+y)-ex)/(ey-e(x+y))

=>dy/dx=ex(ey-1)/ey(1-ex)

dy/dx=ex(ey-1)/ey(1-ex)

### Question 30. If cosy = xcos(a+y). Then Prove that, dy/dx = (cos2(a+y))/sin a

Solution:

We have,

cosy=x*cos(a+y)

Differentiating it with respect to x,

d(cosy)/dx=d(x*cos(a+y))/dx

=>-siny(dy/dx)=cos(a+y)-xsin(a+y)(dy/dx)

=>xsin(a+y)(dy/dx)-siny(dy/dx)=cos(a+y)

=>(dy/dx)(xsin(a+y)-siny)=cos(a+y)

=>dy/dx=(cos(a+y))/(x*sin(a+y)-siny)

Also, x=cosy/cos(a+y)

Substituting it in the earlier statement,

(dy/dx)=(cos(a+y))/((cosy)sin(a+y)/cos(a+y))-siny)

=>dy/dx=cos2(a+y)/(cosy*sin(a+y)-siny(cos(a+y)))

=>dy/dx=cos2(a+y)/(sin(a+y-y))

=>dy/dx=cos2(a+y)/sin(a)